Inorganic / organic composite electrochromic film device and method for manufacturing the same

CN121209169BActive Publication Date: 2026-10-20SUZHOU CHUANGXIN MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511761865.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-27
Publication Date
2026-10-20
Estimated Expiration
2045-11-27

AI Technical Summary

Technical Problem

[0005]本申请的目的在于克服电致变色膜器件中无机材料反应慢、有机材料稳定性差等问题,实现快速变色与长期稳定性,本申请的无机/有机复合电致变色膜器件,包括在导电基板上依次形成的阴极变色材料层、电解质层、阳极变色材料层;

Benefits of technology

阴极变色层采用200nm-400nm厚度的三氧化钨,阳极变色层采用100nm-300nm厚度的二茂铁,通过无机/有机材料复合结构平衡了无机材料的稳定性与有机材料的快速响应特性,光学调制幅度高,褪色时间、着色时间短,且100次循环后透光率变化无劣化,对稳定性与响应速度的双重提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121209169B_ABST
    Figure CN121209169B_ABST
Patent Text Reader

Abstract

The application relates to an inorganic / organic composite electrochromic film device and a manufacturing method thereof. The device comprises a cathode color-changing material layer, an electrolyte layer and an anode color-changing material layer which are sequentially stacked on a conductive substrate. The cathode color-changing material layer is tungsten trioxide with a thickness of 200-400 nm, the anode color-changing material layer is ferrocene with a thickness of 100-300 nm, and the electrolyte layer is a gel-state polymer-based electrolyte with a thickness of 15-45 mu m, which comprises LiClO4 or LiPF6 lithium salt dispersed in a PEO or PMMA matrix. The manufacturing method of the device comprises forming a tungsten trioxide layer by vacuum plating, forming a gel electrolyte layer by solution coating, and forming a ferrocene layer by a spin coating process. Through the composite structure design of inorganic and organic materials and the interface optimization, the electrochromic device is improved in response speed, cycle stability and large-area preparation uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochromic device technology, and in particular to an inorganic / organic composite electrochromic film device and its manufacturing method. Background Technology

[0002] Electrochromic technology is widely used in smart windows, rearview mirrors, electronic paper, and wearable devices. Its core lies in the reversible optical changes that occur in materials under the influence of an external electric field. Current technologies are mainly divided into two systems: inorganic and organic. Inorganic materials, with their high chemical stability, durability, and radiation resistance, have been commercialized in applications such as energy-efficient building windows and anti-glare rearview mirrors. Their color-changing mechanism is based on an electron-ion dual-injection model, exhibiting large visible light modulation amplitude and high cycle life, but they suffer from limitations such as single color and slow response speed. Organic materials, prepared through colloidal crystal template methods or spin-coating processes, possess advantages such as rapid color-changing capabilities, high transparency, and multi-color transformation, but their long-term stability is insufficient, and their cycle reversibility is easily affected by environmental factors.

[0003] In existing technologies, the development of inorganic / organic composite electrochromic materials has become one of the directions for breaking through the performance bottleneck of single systems. For example, through nanostructure design (such as TiO2 nanorod arrays, core-shell structures), the interfacial bonding force and charge transport efficiency between organic materials and inorganic substrates can be improved. Combined with vacuum deposition (such as magnetron sputtering) and coating processes (such as sol-gel method, spin coating), electrochromic systems with simple structures and controllable costs can be realized. However, such composite technologies still face challenges. The interfacial compatibility problem between inorganic and organic materials leads to low charge transport efficiency and decreased cycle stability. Matching the process parameters of vacuum deposition and coating processes is difficult, easily resulting in poor film uniformity, weak adhesion, or crack defects. In addition, the high cost of large-area uniform deposition technology and rare metals limits large-scale application.

[0004] In summary, although existing technologies have made some progress in optimizing the performance of inorganic / organic composite electrochromic materials, how to achieve highly stable, fast-response, and low-cost inorganic / organic composite electrochromic film devices through collaborative innovation in material design and manufacturing processes remains an urgent technical problem to be solved. Summary of the Invention

[0005] The purpose of this application is to overcome the problems of slow reaction of inorganic materials and poor stability of organic materials in electrochromic film devices, and to achieve rapid color change and long-term stability. The inorganic / organic composite electrochromic film device of this application includes a cathode color-changing material layer, an electrolyte layer and an anode color-changing material layer formed sequentially on a conductive substrate. The electrolyte layer includes a lithium salt dispersed in a polymer matrix, wherein the lithium salt is LiClO4 or LiPF6, and the polymer matrix is ​​PEO or PMMA; The thickness of the cathode color-changing material layer is in the range of 200nm-400nm, the thickness of the anode color-changing material layer is in the range of 100nm-300nm, and the thickness of the electrolyte layer is in the range of 15μm-45μm.

[0006] In one embodiment, the electrolyte layer is in a gel state.

[0007] In one embodiment, the cathode color-changing material layer is tungsten trioxide.

[0008] In one embodiment, the anodic color-changing material layer is ferrocene.

[0009] In one embodiment, the anodic color-changing material layer comprises a polymer matrix material in the electrolyte layer.

[0010] In one embodiment, the content of the polymer matrix material gradually decreases in the direction of the conductive substrate toward the anodic color-changing material.

[0011] In one embodiment, the conductive substrate is ITO or FTO.

[0012] This application further provides a method for manufacturing an inorganic / organic composite electrochromic film device, including: A tungsten trioxide layer is formed on the surface of a conductive substrate, wherein the tungsten trioxide layer serves as a cathode color-changing material layer; An electrolyte layer is formed on the tungsten trioxide layer; An anodic color-changing material layer is formed on the electrolyte layer; The electrolyte layer includes a lithium salt dispersed in a polymer matrix, wherein the lithium salt is LiClO4 or LiPF6, and the polymer matrix is ​​PEO or PMMA.

[0013] In one embodiment, the specific steps for forming the electrolyte layer include using polyethylene oxide as a polymer matrix, adding lithium perchlorate, stirring thoroughly in an inert atmosphere to form a transparent electrolyte colloid, and coating the transparent electrolyte colloid onto the tungsten trioxide layer.

[0014] In one embodiment, the specific steps for forming the anodic color-changing material layer include dissolving ferrocene in acetone to form a ferrocene solution, and spin-coating the ferrocene solution onto the electrolyte layer.

[0015] Compared with the prior art, this application has the following beneficial effects: The cathode color-changing layer uses tungsten trioxide with a thickness of 200nm-400nm, and the anode color-changing layer uses ferrocene with a thickness of 100nm-300nm. The inorganic / organic material composite structure balances the stability of inorganic materials and the fast response characteristics of organic materials, resulting in high optical modulation amplitude, short fading and coloring time, and no degradation in transmittance after 100 cycles, thus achieving a dual improvement in stability and response speed.

[0016] The electrolyte layer employs a polymer matrix and lithium salt composite system with a thickness of 15μm-45μm. The gel-state electrolyte is stirred under an inert atmosphere to form a uniform ion-conducting network, achieving a good balance between ionic conductivity and thermal stability. The manufacturing method utilizes a compatible design of vacuum deposition and solution coating processes, enabling large-area fabrication with minimal differences between the center and edge regions and small coloring time errors. Furthermore, in a further technical solution, the anodic color-changing layer contains the same polymer matrix material as the electrolyte layer, enhancing the inorganic / organic interfacial bonding and avoiding the cycle life degradation problem caused by interfacial defects in traditional composite structures.

[0017] In summary, this application achieves rapid response, high stability, low cost, and large-area uniformity through systematic optimization of material selection, thickness control, electrolyte formulation, and manufacturing process. It solves the problems of slow response of inorganic materials, poor stability of organic materials, and insufficient process compatibility in the prior art. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the structure of an organic / organic composite electrochromic film device in one embodiment of this application; Figure 2 This is a flowchart of a method for manufacturing an inorganic / organic composite electrochromic film device according to one embodiment of this application.

[0019] Explanation of reference numerals in the attached figures: 100, conductive substrate; 200, cathode color-changing material layer; 300, electrolyte layer; 400, anode color-changing material layer; 500, top electrode. Detailed Implementation

[0020] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.

[0021] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to such process, method, product, or apparatus.

[0022] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0023] In existing technologies, inorganic electrochromic materials (such as tungsten trioxide, WO3) possess high chemical stability and long cycle life, but suffer from limitations such as slow response speed and limited color range. Organic electrochromic materials (such as ferrocene), while exhibiting rapid color-changing capabilities and multi-color conversion characteristics, face issues of insufficient stability and easy degradation of cycle reversibility. To overcome the performance bottlenecks of single-material systems, this application achieves a synergistic improvement in response speed and stability through the design of a composite structure using inorganic / organic materials and optimization of the manufacturing process. Please refer to [link / reference]. Figure 1 In a preferred embodiment of this application, the inorganic / organic composite electrochromic film device includes a cathode chromic material layer 200, an electrolyte layer 300, and an anodic chromic material layer 400 sequentially formed on a conductive substrate 100. The electrolyte layer 300 includes a lithium salt dispersed in a polymer matrix, wherein the lithium salt is LiClO4 or LiPF6, and the polymer matrix is ​​PEO or PMMA. The thickness of the cathode chromic material layer 200 is in the range of 200nm-400nm, the thickness of the anodic chromic material layer 400 is in the range of 100nm-300nm, and the thickness of the electrolyte layer 300 is in the range of 15μm-45μm.

[0024] The inorganic / organic composite electrochromic film device described in this application comprises a three-layer structure consisting of a cathode color-changing material layer 200, an electrolyte layer 300, and an anode color-changing material layer 400 sequentially formed on a conductive substrate 100. The cathode color-changing material layer 200 uses tungsten trioxide (WO3) with a thickness of 200nm-400nm. This thickness range is achieved through radio frequency magnetron sputtering to ensure the high chemical stability and long cycle life of the inorganic material. At the same time, the ion diffusion path is optimized by controlling the thickness, which can shorten the coloring time and fading time. The electrolyte layer 300 is composed of a polymer matrix and a lithium salt composite, and a gel-state ion conduction network is formed by an inert atmosphere stirring process. The anode color-changing material layer 400 uses ferrocene and can be prepared by spin coating with acetone solution. Its thickness range is compatible with the polymer matrix material. Ferrocene is the main component and independently serves as the functional material of the anode color-changing material layer.

[0025] In the inorganic / organic composite electrochromic film device, the electrolyte layer 300 is set in a gel state. Through the synergistic effect of material selection, structural configuration, and preparation process, technical problems such as poor contact at the solid electrolyte interface and easy leakage of liquid electrolyte are solved. The main material of the gel electrolyte layer 300 is a polymer matrix, such as polyethylene oxide (PEO) or polymethyl methacrylate (PMMA), with lithium salts (such as LiClO4 or LiPF4) dispersed inside. This gel state is formed by the reaction of the functional groups of amino monomers and epoxy monomers to form an organic gel network structure, or by swelling and solidifying the polymer matrix (such as PMMA, PVDF-HFP) with plasticizers (such as propylene carbonate) and lithium salts in a solvent. The three-dimensional network structure can effectively bind liquid electrolyte components (such as propylene carbonate-dimethyl carbonate mixed solvent) to form a stable ion conduction channel. Its thickness is controlled within the range of 15μm–45μm, which ensures ionic conductivity while reducing internal resistance and avoiding stress concentration at the interlayer interface. This allows the ionic conductivity to be maintained at a high level and has a wide electrochemical window, thereby supporting the stability of the device during repeated coloring / bleaching cycles.

[0026] The viscoelastic properties of the gel electrolyte layer 300 enable it to form a tight interfacial contact with the electrochromic layers on both sides (such as the tungsten trioxide cathode layer and the ferrocene anode layer), reducing the risk of interfacial delamination caused by rigid contact in traditional solid electrolytes, while avoiding leakage or corrosion problems that may occur with liquid electrolytes. The film formation process for gel electrolytes typically involves solution coating, for example, stirring polyethylene oxide (PEO) and lithium perchlorate in an inert atmosphere to form a transparent colloid, which is then coated onto the tungsten trioxide layer. This process has good compatibility with vacuum deposition (for inorganic layers) and spin coating (for organic layers), facilitating the achievement of large-area uniform film formation. Furthermore, by adjusting the addition ratio of crosslinking agents (such as triglycidyl-p-aminophenol) or dehydrating agents (such as acetic anhydride), the crosslinking density of the gel network can be controlled, thereby optimizing the balance between its mechanical strength and ion diffusion rate. For example, in gel electrolytes based on amino-terminated polyimide resins, the amide bonds in the molecular chain provide additional coordination sites, enhancing the adhesion to the electrode material and thus improving the cycle life of the device.

[0027] The cathodic chromic material layer 200 is specifically selected as tungsten trioxide (WO3), and the microstructure design of the tungsten trioxide layer affects its electrochromic performance. Preferably, a porous WO3 thin film structure is adopted, which can form a loose and porous surface morphology, providing more channels for ion / electron diffusion. This not only increases the electrochemical active area and improves the current density, but also accelerates the ion implantation / extraction rate, thereby shortening the response time. In addition, an amorphous / microcrystalline dual-phase WO3 heterostructure (such as a composite of a pulsed electrodeposited amorphous layer and a spin-coated-pyrolytic microcrystalline layer) can be further constructed through phase interface engineering. The microcrystalline framework can reduce the charge transfer resistance, maintain a high charge capacity after long-term cycling, and improve the interface strength, thereby enhancing the adhesion between the film layer and the conductive substrate 100. In one specific embodiment, the cathodic chromic material layer 200 is composed only of tungsten trioxide.

[0028] The tungsten trioxide layer can be deposited using methods such as pulsed laser deposition, electrodeposition, or reactive magnetron sputtering. Pulsed electrodeposition allows for the doping of heteroatoms (such as molybdenum) at room temperature and atmospheric pressure. The dopant elements improve the material's conductivity and increase surface electrochemical active sites, further optimizing charge transport efficiency. Furthermore, by using a sol-gel method and introducing additives such as polyethylene glycol or polypropylene carbonate into the precursor, the film's density and ion transport pathways can be improved, resulting in all-solid-state devices with excellent thermal insulation and cycle stability. In this preferred embodiment, the cathodic chromic material layer 200 consists only of tungsten trioxide and polyethylene glycol or tungsten trioxide and polypropylene carbonate, with the polyethylene glycol or polypropylene carbonate content controlled to be less than 10%.

[0029] The anodic color-changing material layer 400 is specifically chosen to be ferrocene. Ferrocene molecules have a sandwich structure, in which iron atoms are located between two cyclopentadienyl rings. This structure endows it with good redox reversibility. By introducing appropriate electron-pulling substituents (such as carboxyl groups, acetyl groups, etc.) onto its ferrocene rings, its frontier orbital energy levels can be tuned, thereby enhancing its electrochromic properties. For example, when strong electron-pulling groups and weak electron-withdrawing groups are introduced into ferrocene derivatives, its oxidation state (Fe...)... 3+ The stability and reversibility of the ferrocene are improved, thereby achieving more stable optical switching during the electrochromic process. In a preferred embodiment, by combining ferrocene with a polymer matrix (such as PEO or PMMA), the dissolution or aggregation of active materials can be further suppressed, extending the device lifespan. In this embodiment, the content of the polymer matrix is ​​controlled to be less than 20%, and the polymer plays an auxiliary role. The anodic color-changing material layer 400 consists only of ferrocene and the polymer matrix, without any other substances. In a specific embodiment, the anodic color-changing material layer containing only ferrocene can be formed by spin-coating after dissolving in acetone solution. Alternatively, a polymer can be further added to the solution, and after the solution evaporates, an anodic color-changing material layer containing ferrocene and the polymer can be formed.

[0030] In the inorganic / organic composite electrochromic film device, the anodic color-changing material layer 400 contains the same polymer matrix material (such as PEO or PMMA) as the electrolyte layer 300. Introducing the same polymer matrix (such as PEO or PMMA) into the anodic color-changing material layer 400 as the gel electrolyte layer 300 can effectively reduce the degree of micro-phase separation at the interface between the two phases. For example, when the anode layer uses a composite system of ferrocene dispersed in a PEO matrix, and the electrolyte layer 300 is a PEO / LiClO4 gel, the two have similar molecular chain segment structures, and interpenetrating or entangled transition regions can be formed at the interface.

[0031] Furthermore, a top electrode 500 can be further provided, located on the anodic color-changing material layer 400, to provide electrical connection. The conductive substrate 100 can directly serve as the bottom electrode. In a preferred embodiment, the structure consists only of the conductive substrate 100, the cathodic color-changing material layer 200, the electrolyte layer 300, the anodic color-changing material layer 400, and the top electrode 500. No additional layers are provided between these layers. Using the approach of this application, other functional layers can be omitted, such as isolation layers and storage layers, greatly simplifying the structure. The electrode layers also do not require extensive modifications.

[0032] Furthermore, designing a gradient distribution with a gradually decreasing content of polymer matrix material (such as PMMA) in the direction of the conductive substrate 100 toward the anodic color-changing layer is a technical measure to optimize the distribution of interfacial stress. This gradient structure can be achieved through layer-by-layer coating, so that the anodic layer has a higher polymer content near the electrolyte side, promoting interfacial compatibility; while the polymer content decreases near the conductive substrate 100 side, and the proportion of electrochromic active material (such as ferrocene) increases accordingly, ensuring effective reaction and alleviating internal stress caused by differences in the coefficient of thermal expansion or modulus between different layers. During device bending or thermal cycling, it can reduce the risk of interfacial peeling or cracking.

[0033] From a fabrication process perspective, sharing the same polymer matrix material between the anode layer and electrolyte layer 300 improves process compatibility and interface integrity. For example, after the electrolyte layer 300 (PEO-based gel) has cured, when spin-coated with a ferrocene-PEO mixed solution dissolved in the same solvent (such as acetonitrile), the surface of the lower gel layer may swell slightly, causing physical cross-linking or interpenetration of chain segments at the interface between the two phases. This enhanced interfacial fusion strengthens interlayer adhesion, facilitating uniform film formation on large-area substrates and reducing defects. For flexible devices, this structural design can withstand certain mechanical deformations.

[0034] The conductive substrate 100 is ITO or FTO. Both ITO and FTO are transparent conductive oxide (TCO) materials, whose characteristics meet the requirements of electrochromic devices. They have high conductivity and high transmittance in the visible light region, meeting the requirements for low driving voltage and high transmittance.

[0035] Please see Figure 2 This application further provides a method for manufacturing an inorganic / organic composite electrochromic film device, comprising: forming a tungsten trioxide layer on the surface of a conductive substrate 100, wherein the tungsten trioxide layer serves as a cathode color-changing material layer 200; forming an electrolyte layer 300 on the tungsten trioxide layer; and forming an anode color-changing material layer 400 on the electrolyte layer 300; wherein the lithium salt is dispersed in a polymer matrix, the lithium salt being LiClO4 or LiPF6, and the polymer matrix being PEO or PMMA.

[0036] The method for manufacturing inorganic / organic composite electrochromic film devices provided in this application includes a specific layer sequence design, material system selection, and process step combination. The core of this method lies in the sequential formation of a tungsten trioxide cathode color-changing layer, a polymer-based electrolyte layer 300, and an anodic color-changing material layer 400. This layer sequence design ensures that ions can migrate directionally along the direction of conductive substrate 100 → tungsten trioxide layer → electrolyte layer 300 → anode layer under the influence of an electric field, conforming to the ion-electron dual-injection model required for the electrochromic reaction. The process combination (especially the combination of vacuum deposition for the inorganic layer and solution coating for the organic / gel layer) provides a feasible solution to the interface compatibility problem during large-area film formation. For example, first forming a dense and strongly adherent tungsten trioxide layer on the conductive substrate 100 through vacuum deposition (such as sputtering), and then coating the gel electrolyte layer 300 using a solution method, helps reduce interlayer defects.

[0037] A tungsten trioxide layer is formed on the surface of a conductive substrate 100 as a cathode chromatic material layer 200, including control of the thin film's crystalline structure and thickness. Tungsten trioxide films are prone to forming an amorphous structure when prepared below 300°C, and amorphous tungsten trioxide exhibits higher coloring efficiency and a shorter response time compared to crystalline structures. The manufacturing method can optimize the electrochromic performance by maintaining the tungsten trioxide layer in an amorphous state by adjusting parameters such as deposition temperature. Simultaneously, the cathode layer thickness is controlled within the range of 200 nm to 400 nm.

[0038] An electrolyte layer 300 is formed on the tungsten trioxide layer, wherein the electrolyte comprises a lithium salt (LiClO4 or LiPF6) dispersed in a polymer matrix (such as PEO or PMMA), and the electrolyte layer 300 is in a gel state. The advantage of this technique is that the liquid electrolyte components are bound by a three-dimensional network structure in a gel state, forming stable ion transport channels. The preparation process typically involves thoroughly stirring the polymer matrix (such as polyethylene oxide, PEO) and the lithium salt (such as lithium perchlorate, LiClO4) in an inert atmosphere to form a transparent colloid, which is then coated onto the tungsten trioxide layer. The thickness of the gel electrolyte layer 300 is set between 15 and 45 micrometers to ensure ionic conductivity while reducing internal resistance and avoiding interlayer stress caused by excessive thickness. This gel-state design also allows for close interfacial contact with the upper and lower layers, reducing interfacial impedance.

[0039] An anodic color-changing material layer 400 is formed on the electrolyte layer 300. The anodic color-changing material layer 400 may contain the same polymer matrix material (such as PEO or PMMA) as the electrolyte layer 300, and may be designed such that the content of the polymer matrix material gradually decreases in the direction from the conductive substrate 100 toward the anode layer. This gradient composition design can be achieved through a solution coating process (such as spin coating), for example, dissolving ferrocene in acetone and mixing it with PEO before spin coating it onto the gel electrolyte layer 300. During film formation, the slight swelling effect of the solvent on the surface of the underlying gel layer allows for interpenetrating chain segments at the interface between the two phases, thereby enhancing interlayer adhesion. Through the above-mentioned layer sequence design, material selection, and process parameter control, ion transport efficiency, interfacial bonding strength, and device integration feasibility are optimized.

[0040] The specific steps for forming the electrolyte layer 300 include using polyethylene oxide as the polymer matrix, adding lithium perchlorate, thoroughly stirring in an inert atmosphere to form a transparent electrolyte colloid, and coating the transparent electrolyte colloid onto the tungsten trioxide layer. Specifically, polyethylene oxide (PEO, i.e., polyethylene oxide) can be used as the polymer matrix, based on the fact that the ether oxygen atoms (-O-) in its molecular chain can react with lithium ions (Li). + This property allows for coordination, thereby forming ion transport channels. When lithium perchlorate (LiClO4) is added as a lithium salt, Li... + It will solvate with the ether oxygen groups of PEO, thereby establishing a continuous ion migration pathway in the polymer matrix. To ensure the stability of ionic conductivity, the molecular weight of PEO is usually controlled in the range of 100,000 to 4 million.

[0041] Thorough stirring is performed in an inert atmosphere (such as argon or nitrogen) to prevent side reactions between the lithium salt and water vapor or oxygen. Stirring must continue until a homogeneous, transparent colloidal state is formed, indicating that the lithium salt has fully dissociated and distributed within the PEO matrix, forming a homogeneous ionic conductor. When coating the formed transparent electrolyte colloid onto the tungsten trioxide (WO3) cathode layer, the rheological properties of the colloid and coating parameters (such as coating speed and thickness) must be controlled synergistically. The electrolyte layer thickness is set within the range of 15 μm–45 μm, which can be achieved by adjusting the coating gap or colloid concentration. After coating, the gel electrolyte precursor can be cured by solvent evaporation or mild heat treatment (e.g., below 60°C). During this process, PEO segments may form physical adsorption or weak interactions with the WO3 layer surface, thereby enhancing interlayer adhesion and reducing interfacial impedance.

[0042] The specific steps for forming the anodic color-changing material layer 400 include dissolving ferrocene in acetone to form a ferrocene solution, and then spin-coating the ferrocene solution onto the electrolyte layer 300. Acetone can effectively dissolve ferrocene and its derivatives (such as 11-bromo-undecylferrocene) to form a homogeneous and stable solution. In practice, the concentration of the ferrocene solution is typically controlled within the range of 0.5% to 5% (mass fraction) to ensure that the solution has suitable viscosity and volatility, thereby obtaining a film of uniform thickness in the subsequent spin-coating process. In specific operation, the spin-coating speed is typically set within the range of 1000 rpm to 3000 rpm, and the spin-coating time lasts for 30 to 60 seconds. During this process, the acetone solvent evaporates rapidly, and ferrocene molecules precipitate on the surface of the gel electrolyte layer 300 to form a solid film. The coordinated control of rotation speed and time directly affects the final thickness of the film (target range of 100nm to 300nm) and surface roughness. This allows the surface roughness of the ferrocene film to be controlled within a certain range, which helps to reduce interface defects, lower the ion migration barrier, and thus improve the response speed of the device. The coloring / fading time can be shortened to the order of seconds. To ensure that the redox activity of the ferrocene film is not affected by the environment, the entire spin-coating process is carried out in an inert atmosphere (such as argon or nitrogen). Specific Implementation Example 1 This embodiment illustrates the fabrication process of a basic inorganic / organic composite electrochromic element. First, ITO conductive glass with a surface resistivity below 10 Ω / sq is selected as the substrate and subjected to ultrasonic cleaning, pure water rinsing, and drying. Subsequently, a 300 nm thick tungsten trioxide (WO3) film is deposited on the substrate surface as the cathode electrochromic material layer using radio frequency magnetron sputtering. During sputtering, the substrate temperature is maintained at 150°C, the working pressure at 0.5 Pa, and the sputtering power at 200 W.

[0044] The electrolyte layer uses polyethylene oxide (PEO) as the polymer matrix, with 0.5 M lithium perchlorate (LiClO4) added. The mixture is stirred thoroughly for 4 hours under a nitrogen atmosphere to form a transparent electrolyte colloid. This colloid is then uniformly coated onto the surface of a WO3 film to form a gel electrolyte layer with a thickness of 30 μm. Subsequently, a 0.1 M ferrocene acetone solution is spin-coated onto the electrolyte layer. By controlling the spin-coating speed at 2000 rpm and the time at 30 seconds, an anodic color-changing material layer with a thickness of approximately 200 nm is formed.

[0045] Finally, the device was packaged and its electrochromic performance was tested. Under ±2.5 V square wave pulse voltage, the device exhibited a stable color-changing response. Test data showed that at a wavelength of 550 nm, the transmittance decreased from 70% to 15%, and the optical contrast ΔT reached 55%. The coloring reaction time was 1.8 seconds, and the fading reaction time was 2.3 seconds. After 100 switching cycles, no significant degradation in optical performance was observed, confirming that the device structure has rapid color-changing characteristics and good durability at room temperature.

[0046] Example 2 This embodiment focuses on the impact of electrolyte composition optimization on device thermal stability. Compared with Embodiment 1, the main differences are: the polymer matrix of the electrolyte layer is changed to polymethyl methacrylate (PMMA), the lithium salt is changed to lithium hexafluorophosphate (LiPF6), the thickness of the WO3 cathode layer is increased to 400 nm, the thickness of the electrolyte layer is 40 μm, and the concentration of the ferrocene solution is increased to 0.2 M.

[0047] In the specific preparation process, the WO3 layer was still prepared using radio frequency magnetron sputtering, but the thickness was increased to 500 nm by extending the sputtering time. The electrolyte layer was prepared by mixing PMMA and 0.8 M LiPF6 in a nitrogen atmosphere to form a colloid, which was then coated and cured to form a 40 μm thick gel electrolyte. The anode layer was prepared by spin-coating with a 0.2 M ferrocene acetone solution, with the spin-coating parameters adjusted to 1500 rpm and 40 seconds.

[0048] Thermal stability tests were conducted on the optimized components. The results showed that the ΔT retention rate was 99.2% at 25°C, 97.8% at 60°C, and still maintained 92.3% at a high temperature of 85°C. This data confirms that the electrolyte using the PMMA / LiPF6 system exhibits superior stability under high-temperature conditions and is suitable for applications over a wider temperature range.

[0049] Example 3 This embodiment verifies the feasibility of this technical solution for large-area fabrication. A 5cm × 5cm FTO conductive glass substrate was used. First, a WO3 thin film with a thickness controlled at 350 nm was deposited on the substrate surface via spray pyrolysis. The electrolyte layer consisted of a colloid composed of PEO and 0.6 M LiClO4, which was applied using a slot coating method to form a uniform film with a thickness of 35 μm. The anode layer used a 0.15 M ferrocene solution, and a large-area uniform film was formed through an automated spray coating process.

[0050] The uniformity of performance of the fabricated large-area components was tested, and the results showed that the difference in optical contrast ΔT between the central and edge regions of the components was less than 5%, and the coloring time error was controlled within ±0.3 seconds. These results demonstrate that the process route combining vacuum deposition and solution coating used in this technical solution has good scalability and can meet the process requirements for large-area applications.

[0051] The above embodiments collectively demonstrate that by combining the composite design of inorganic materials (WO3) and organic materials (ferrocene) with the optimization of the gel electrolyte layer, a comprehensive improvement in the electrochromic device's fast response, thermal stability, and large-area uniformity has been achieved. All embodiments employ a low voltage drive of ±2.5 V, exhibiting good practicality and energy efficiency.

[0052] As described above, this application provides an inorganic / organic composite electrochromic film device and its manufacturing method. The device includes a cathode color-changing material layer, an electrolyte layer, and an anode color-changing material layer sequentially stacked on a conductive substrate. The cathode color-changing material layer is tungsten trioxide, with a thickness controlled in the range of 200 nm to 400 nm, and can be prepared using processes such as radio frequency magnetron sputtering. The material and thickness selection take into account both chemical stability and optimized ion diffusion paths. The anode color-changing material layer is ferrocene, with a thickness of 100 nm to 300 nm, and can be formed by solution methods (such as spin coating). The electrolyte layer is in a gel state, composed of a polymer matrix (PEO or PMMA) and a lithium salt (LiClO4 or LiPF6). This gel electrolyte is prepared by stirring under an inert atmosphere to form a homogeneous colloid and then coating it. Its three-dimensional network structure helps to form stable ion channels and improve interlayer interface contact.

[0053] The device fabrication method includes the steps of sequentially forming the aforementioned functional layers: preparing an inorganic cathode layer by vacuum deposition (e.g., sputtering), forming a gel electrolyte layer by solution coating, and preparing an organic anode layer by spin coating. This fabrication method places particular emphasis on interface control, allowing the anode layer to contain the same polymer matrix material as the electrolyte layer, and enabling the design of composition gradients to optimize interfacial stress distribution. Through the synergistic design of the aforementioned material system, layered structure, and fabrication process, the electrochromic film device achieves a combination of the stability of inorganic materials and the rapid response characteristics of organic materials.

[0054] The above is only one specific implementation of this application, and any other improvements made based on the concept of this application shall be considered within the scope of protection of this application.

Claims

1. An inorganic / organic composite electrochromic film device, characterized in that, Includes a cathode color-changing material layer, an electrolyte layer, and an anode color-changing material layer formed sequentially on a conductive substrate; The electrolyte layer includes a lithium salt dispersed in a polymer matrix, wherein the lithium salt is LiClO4 or LiPF6, and the polymer matrix is ​​PEO or PMMA; The anodic color-changing material layer further includes the polymer matrix, and the content of the polymer matrix in the anodic color-changing material layer gradually decreases in the direction from the side of the anodic color-changing material layer closer to the electrolyte layer to the side farther away from the electrolyte layer; The electrolyte layer is in a gel state, the cathode color-changing material layer is tungsten trioxide, and the anode color-changing material layer is ferrocene; The thickness of the cathode color-changing material layer is in the range of 200nm-400nm, the thickness of the anode color-changing material layer is in the range of 100nm-300nm, and the thickness of the electrolyte layer is in the range of 15μm-45μm.

2. The inorganic / organic composite electrochromic film device according to claim 1, characterized in that, The anodic color-changing material layer consists only of ferrocene and the polymer matrix.

3. The inorganic / organic composite electrochromic film device according to claim 1, characterized in that, It also includes a top electrode disposed on the anode color-changing material layer, and the conductive substrate serves as the bottom electrode; the inorganic / organic composite electrochromic film device is composed of the conductive substrate, the cathode color-changing material layer, the electrolyte layer, the anode color-changing material layer and the top electrode.

4. The inorganic / organic composite electrochromic film device according to claim 1, characterized in that, The conductive substrate is ITO or FTO.

5. A method for manufacturing an inorganic / organic composite electrochromic film device, used to manufacture the inorganic / organic composite electrochromic film device as described in any one of claims 1-4, characterized in that, include: A tungsten trioxide layer is formed on the surface of a conductive substrate, wherein the tungsten trioxide layer serves as a cathode color-changing material layer; An electrolyte layer is formed on the tungsten trioxide layer; An anodic color-changing material layer is formed on the electrolyte layer by a layer-by-layer coating method. The anodic color-changing material layer includes the same polymer matrix as the electrolyte layer. Through the layer-by-layer coating, the content of the polymer matrix in the anodic color-changing material layer gradually decreases in the direction from the side of the anodic color-changing material layer closer to the electrolyte layer to the side farther away from the electrolyte layer. The electrolyte layer includes a lithium salt dispersed in a polymer matrix. The lithium salt is either LiClO4 or LiPF6, and the polymer matrix is ​​either PEO or PMMA.

6. The method for manufacturing an inorganic / organic composite electrochromic film device according to claim 5, characterized in that, The specific steps for forming the electrolyte layer include using polyethylene oxide as the polymer matrix, adding lithium perchlorate, stirring thoroughly in an inert atmosphere to form a transparent electrolyte colloid, and coating the transparent electrolyte colloid onto the tungsten trioxide layer.

7. The method for manufacturing an inorganic / organic composite electrochromic film device according to claim 5, characterized in that, The specific steps for forming the anodic color-changing material layer include: dissolving ferrocene in acetone and adding the same polymer matrix as the electrolyte layer to form multiple ferrocene solutions with different polymer matrix contents; and spin-coating the multiple ferrocene solutions onto the electrolyte layer in sequence according to the order in which the polymer matrix content in the multiple ferrocene solutions gradually decreases.

Citation Information

Patent Citations

  • Electrochemical energy storage devices

    CN106660977A

  • Gel electrolyte, preparation method thereof and electrochromic device

    CN119708736A